NEGATIVE IMPLICATIONS OF CRIMINAL ACTION FOR FEMALE CHILD TRAFFICKING VICTIMS IN INDONESIA - Hamja, Hamja; Maulana, Kodir; Susanto, Asep (jfpublisher, 2023)
Girls are a group that is highly susceptible to the human trafficking crime. Even so, there were still very few researches on this crime from the victim's perspective. This research aims to identify various negative implications caused by human trafficking crime based on the victim's perspective through a victimological approach. The method used in this research is a qualitative method with a normative juridical approach. The data used in this research is primary data obtained from several informants, these are Health Extension Officer Kusuma Bongas and several victims who were survivors of human trafficking, through in-depth interviews and observations. According to the research findings, human trafficking is a serious crime that has a wide-ranging take effect across multiple sectors. In addition to social effects, human trafficking has negative legal consequences as well as it leads to various criminal offenses such as prostitution, the physical, sexual, and psychological exploitation of children, violations of labor laws, and other crimes. For the victims of this crime, there is still potential for unfairness and legal ambiguity due to the law's imperfect implementation in this subject. Therefore, it is important to improve the judiciary system, specifically the fair and strict laws against the human trafficking crime, in order to provide victims safeguards and have a deterrent impact on offenders.